2005
DOI: 10.1002/ijc.21534
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of proteasome activity, nuclear factor-KB translocation and cell survival by the antialcoholism drug disulfiram

Abstract: The proteasome pathway is an important target for anticancer drug development. Here, we identify the antialcoholism drug disulfiram and its analogue pyrrolidine dithiocarbamate (PDTC) as inhibitors of the 26S proteasome activity in a cell-based screening assay. As expected for proteasome inhibitors, these compounds also inhibited TNF-a-induced nuclear factor-KB (NF-KB) translocation and were cytotoxic. Disulfiram was more cytotoxic against chronic lymphocytic leukemia cells compared to peripheral blood mononuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
94
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(99 citation statements)
references
References 16 publications
5
94
0
Order By: Relevance
“…4). Most recently, one group reported that DSF alone at f0.16 Amol/L has proteasomeinhibitory activity under a cell-based screening assay condition (49). However, under our experimental conditions, DSF at 15 to 20 Amol/L was unable to inhibit cellular proteasome activity in cultured breast cancer cells (Figs.…”
Section: Discussionmentioning
confidence: 52%
“…4). Most recently, one group reported that DSF alone at f0.16 Amol/L has proteasomeinhibitory activity under a cell-based screening assay condition (49). However, under our experimental conditions, DSF at 15 to 20 Amol/L was unable to inhibit cellular proteasome activity in cultured breast cancer cells (Figs.…”
Section: Discussionmentioning
confidence: 52%
“…Disulfiram has been used for decades to treat alcohol abuse, and recently its potential in cancer treatment has been investigated [139]. The anti-cancer mechanisms of disulfiram are not limited to ALDH inhibition; principally, disulfiram is used to inhibit the proteasome and E3 ligases, and may also be a DNAdemethylating compound [140][141][142][143]. Disulfiram inhibits both ALDH1A1 and ALDH2 isoforms [138,144], and has shown anti-CSC effects in breast cancer and GBM [145,146].…”
Section: Aldehyde Dehydrogenase Inhibitorsmentioning
confidence: 99%
“…Disulfiram was first characterized as an inhibitor of aldehyde dehydrogenase, and as such has been used for more than fifty years to prevent relapse in alcohol addicts. Subsequently, disulfiram was found to also inhibit dopamine-β-hydroxylase [43], CYP2E1 [44], and proteasomes [45]; novel applications based on these effects have been proposed [46]. The drug is metabolized rapidly, and it is the metabolites that are responsible for the various inhibitory effects.…”
Section: A Candidate Cyp2e1 Inhibitor: Disulfirammentioning
confidence: 99%